PREVALENCE OF HYPERTENSION IN THE FRENCH GENERAL POPULATION BY AUTOSCREENING OR HOME BLOOD PRESSURE MONITORING: FLAHS 2020 SURVEY. (April 2021) - Girerd, Xavier; Pathak, Atul; Silhol, François; Wimart, Marie Catherine; Hanon, Olivier
Abstract : Objective: To assess the prevalence of hypertension in the general population based on the completion of an autoscreening or self-measurement protocol using an automatic home blood pressure monitor. Design and method: The FLAHS 2020 survey questioned individuals aged 35 and over from the Kantar Health Metascope permanent sample base (a representative panel of the population living in metropolitan France) with the question: Do you have a blood pressure monitor at home? The respondents assessed their blood pressure according to the protocol suiviHTA (6 sessions of 3 measurements, 3 sessions in the morning, 3 sessions in the evening, 3 consecutive days, 1 minute interval between each measurement, sitting position, without getting up between each measurement). The analysis calculated for each subject the average of the 18 measurements (protocol suiviHTA) and the average of the last 2 measurements of the first session (protocol depistHTA). High blood pressure was determined with thresholds >135/85 and >140/90 based on data from both protocols (mmHg). Results: Of the 4069 participants in FLAHS 2020, 827 had a blood pressure monitor of which 488 (59%) were on at least one antihypertensive therapy. With the protocol suiviHTA, the mean BP in treated subjects was 129.0/75.5, compared to 119.5/72.7 in untreated subjects. The table details the % prevalence [IC95] of high blood pressure by blood pressure threshold and protocol: Figure. No caption available. Conclusions: Significant differences in the prevalence of high blood pressure according to the protocol performed are observed, particularly in the population of subjects treated with antihypertensive drugs. With the protocol suiviHTA, which is the one recommended by the French Health Authority, the prevalence of high blood pressure in France is 28% in the population of subjects aged 35 years and over.